TOXOPATHOLOGICAL EFFECTS OF PHENYLMETHANE ON MALE ALBINO MICE INTERNAL ORGANS - Alkaisie, B. I.; Hassan, S. L.; Radam, S. A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
This study was aimed to evaluate the toxic properties of phenylmethane on internal organs and liver enzymes (Alkaline phosphatase (ALP) and Alkaline serum transaminase (AST)changes in mice. Thirty albino mice randomly divided equally into 2 groups, each group contains (15) animals as following: 1st group was administrated orally (0.2 mg / kg B.w) of Phenylmethane daily for (8)weeks, 2nd group was considered as negative control group. Finally all animals euthanized and sample of blood were taken for biochemical examination and histopathological specimens were taken from liver, kidney and brain. Results revealed that phenylmethane pointedly enlarged in the level of liver enzyme after 8 weeks that ALP (88.50 ± 1.01), AST (250.20 ± 0.92) compare with control(50.00 ± 0.85), (231.80 ± 1.40). The histopathological lesions showed that the animals exposed to toxic dose of phenylmethane was characterized by inflammatory reaction, hemorrhage, congested blood vessels, necrosis, fibrosis and granuloma in internal organs. In conclusion, phenylmethane had possess toxic effects for internal organs in mice. To avoid its harm on human, the use of phenylmethane should be expertise.